The protein phosphatase PPM1A dephosphorylates and activates YAP to govern mammalian intestinal and liver regeneration - Zhou, Ruyuan; Wu, Qirou; Wang, Mengqiu; Irani, Seema; Li, Xiao; Zhang, Qian; Meng, Fansen; Liu, Shengduo; Zhang, Fei; Wu, Liming; Lin, Xia; Wang, Xiaojian; et al. (PLoS biology, 2021)
The Hippo-YAP pathway responds to diverse environmental cues to manage tissue homeostasis, organ regeneration, tumorigenesis, and immunity. However, how phosphatase(s) directly target Yes-associated protein (YAP) and determine its physiological activity are still inconclusive. Here, we utilized an unbiased phosphatome screening and identified protein phosphatase magnesium-dependent 1A (PPM1A/PP2Cα) as the bona fide and physiological YAP phosphatase. We found that PPM1A was associated with YAP/TAZ in both the cytoplasm and the nucleus to directly eliminate phospho-S127 on YAP, which conferring YAP the nuclear distribution and transcription potency. Accordingly, genetic ablation or depletion of PPM1A in cells, organoids, and mice elicited an enhanced YAP/TAZ cytoplasmic retention and resulted in the diminished cell proliferation, severe gut regeneration defects in colitis, and impeded liver regeneration upon injury. These regeneration defects in murine model were largely rescued via a genetic large tumor suppressor kinase 1 (LATS1) deficiency or the pharmacological inhibition of Hippo-YAP signaling. Therefore, we identify a physiological phosphatase of YAP/TAZ, describe its critical effects in YAP/TAZ cellular distribution, and demonstrate its physiological roles in mammalian organ regeneration.